Case Study: Recombinant Bromelain Downstream Processing - Amid, Azura; Mohd Arshad, Zatul Iffah; Othman, Muhd. Ezza Faiez (Springer International Publishing, 2015)
This chapter presents details on the purification, formulation and drying of recombinant bromelain. The wide range of applications of recombinant bromelain has increased interest in finding viable purification techniques for large-scale production. An affinity chromatography technique was developed by Amid and co-workers (Expression, purification, and characterization of a recombinant stem bromelain from Ananas comosus, Process Biochem 46:2232–2239, 2011) to purify recombinant bromelain. However, this technique presented low recovery and small sample loading capacity and thus is not suitable as a purification tool in the largescale production of recombinant bromelain. An aqueous two-phase system is one alternative method that we use to purify recombinant bromelain, as it reliable and easy to scale up and has a low cost. As part of avoiding cysteine degradation, spray drying the purified recombinant protein with maltodextrin as an excipient provides the possibility of preserving its activity and creating fine particles that are suitable for end-product application. The processes of the purification, formulation and spray drying of recombinant bromelain are explained briefly.